Financial sanctions, SWIFT, and the architecture of the international payments system - Marco Cipriani; Linda S. Goldberg; Gabriele La Spada (Federal Reserve Bank of New York, 2023)
Financial sanctions, alongside economic sanctions, are components of the toolkit used by governments as part of international diplomacy. The use of sanctions, especially financial, has increased over the last seventy years. Financial sanctions have been particularly important whenever the goals of the sanctioning countries were related to democracy and human rights. Financial sanctions restrict entities-countries, businesses, or even individuals-from purchasing or selling financial assets, or from accessing custodial or other financial services. They can be imposed on a sanctioned entity's ability to access the infrastructures that are in place to execute international payments, irrespective of whether such payments underpin financial or real activity. This article explains how financial sanctions can be designed to limit access to the international payments system and, in particular, the SWIFT network, and provides some recent examples.
Keywords: F3; F51; G15; G2; 330; sanctions; financial sanctions; cross-border payments; SWIFT; Russia-Ukraine war